The Impact of Debt Financing on Startup Profitability - Zhang, Chengzhuo; Azman, Nik Hadiyan Binti Nik (Business Management and Strategy, 2023)
If a start-up company is unable to grow due to a lack of capital, it is prudent to investigate the possibility of using debt as a source of funding. This study examines the impact of debt financing on the profitability of start-ups using trade-off theory and pecking order theory and uses regression analysis to select factors that are correlated with debt financing structure and profitability for listed companies on the National Equities Exchange and Quotation System (NEEQ) from 2012 to 2021. At the end of the theoretical and empirical analyses, the impact of debt financing on the profitability of start-ups is analyzed and corresponding countermeasures are proposed. Finally, the findings of the study are summarized and the shortcomings of the study and the prospects for future research are outlined. The findings of this study are that debt level structure is negatively related to profitability, indicating that gearing has a negative impact on the profitability of start-ups. In terms of debt type structure, mercantile credit has a positive effect on the profitability of start-ups and bank financing have a detrimental effect on profitability. Overall, debt financing has a negative impact on the profitability of start-ups, but business credit has a positive impact on profitability.